Frosted branch angiitis caused by Varicella Zoster virus in an immunocompetent patient - Mahshid Talebi-Taher (Iranian Journal of Microbiology, 2015)
Introduction: Frosted branch angiitis(FBA) is a panuveitis with sheating of all retinal vesssels. Case presentation: Herein we report an immunocompetent person who presented with fever, headache, atypical rash, and hazy vision. Ophthalmoscopy of both eyes revealed perivascular sheathing with frosted branch angiitis pattern in veins, patchy retinal hemorrhages. Aqueous PCR analysis turned positive for VZV. Discussion: This case illustrates that VZV should be considered in the differential diagnosis of retinal perivasculitis. Since a rapid and accurate diagnosis is crucial for prompt administration of antiviral therapy, PCR-based analysis of aqueous humor is a valuable tool for detecting viruses.